Pengembangan Sistem Penjualan dengan Rekomendasi Kompatibilitas Komponen pada Toko Komputer - Abi Sajiwo Binar Swandito; Achmad Arwan; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
In current era, owning a personal computer has became a common thing. In the past, computers could only be found in office buildings or large companies, however, nowdays we find a lot of computers in someone's home. Now computers become a necessity to do daily activities. As time goes by, a lot of people who want to own a personal computer. However, most enthusiasts still don't understand the procedure for selecting components to make a complete personal computer. In addition, there are so many types of components to make a complete personal computer. In addition, there are so manytype of components on the market that makes people easily confused in choosing component. To deal with this problem, the writer made the development of a sales sistem with recommendations for compatibility of computer components so people can choose computer components without worrying about whether the computer components that have been purchased can work properly. In the making of this system using waterfall method as software development lifecycle waterfall method. In the process the software implementasion is done using laravel framework. After the systems complete, testing is carried out with white box testing and black box testing methods. After carrying out the testing stage using white box testing method and black box testing the result are 100% successful.